Taking a Walk in Their Shoes: The Lived Experiences of Emerging Adults with Type 1 Diabetes - Ramchandani, Neesha (Medical Research Archives, 2023)
The period of emerging adulthood, which has been defined as the time from 18-30 years old, is one of the most challenging developmental periods to navigate through because of all of the significant life changes that occur during this time. Add type 1 diabetes to the mix and the period of emerging adulthood becomes even more challenging. This paper is a secondary analysis of a qualitative descriptive study on challenges of diabetes self-management in emerging adults with type 1 diabetes. It presents three vignettes of emerging adults with type 1 diabetes to help clinicians better understand how these individuals view diabetes management and related challenges during this especially critical developmental stage that is rife with transitions. The vignettes exemplify the multitudes of thoughts, feelings, and emotions experienced by emerging adults with type 1 diabetes when dealing with various aspects of their everyday lives. Important takeaway messages include that apparent diabetes mismanagement is usually not due to negligence, females have extreme fear of hypoglycemia, trying to exercise can be frustrating, mature considerations are made when deciding whether or not to drink alcohol, and diabetes technology can be very helpful but is not helpful for everybody. Additionally, regarding diabetes follow-up visits, the emerging adults in this study desired the personal touch of in-person visits. It is hoped that if clinicians are better able to understand what emerging adults with diabetes are going through during this period of time, in their own words, interventions and care plans can be devised to best meet their needs.